Highly efficient, co-solvent assisted glycolytic depolymerization of waste polyethylene terephthalate (PET) into Bis(2-hydroxyethyl) terephthalate (BHET) monomer - Markandeya, Nishant; Solanki, Bhanupratap Singh; Ramalingam, Karthick; Kamble, Sanjay (Industrial & Engineering Chemistry Research, 2025)
Recently, growing use of plastics has led to the accumulation of waste that must be dealt with paramount priority. Among all plastic wastes, polyethylene terephthalate (PET) is the most widely used thermoplastic polyester globally because of its extensive applications in packaging, automotive manufacturing, and textile markets. Thus, there is a need to develop a sustainable and viable PET recycling process. This study presents an efficient solvothermal process for the depolymerization of PET into bis(2-hydroxyethyl) terephthalate (BHET) using co-solvent assisted glycolysis. The process uses N-methylimidazole (NMI) as a cosolvent with ethylene glycol (EG), achieving complete PET conversion and 92% BHET yield under optimized reaction conditions (180 degrees C, 45 min, PET:EG:NMI ratio of 1:7:8) without using a catalyst. The effectiveness of the cosolvent system was attributed to its polarity and H-bonding capabilities, which enhanced polymer swelling and facilitated the depolymerization. SEM analysis revealed pore formation in the NMI-treated PET, whereas FTIR studies confirmed the progressive formation of ester groups during depolymerization of PET. Kinetics studies based on different models indicated that, at higher temperatures, the surface reaction and homogeneous model proved to be rate-controlling due to the elimination of mass transfer limitations. A preliminary technoeconomic analysis and recyclability experiments further supported the scalability potential of the present study.